Chromoendoscopy innovation: Could purple corn solution be a potential natural contrast agent for detecting colonic lesions? - Kishimoto, Gustavo; Yamamoto, Tamy (Revista de Gastroenterología del Perú, 2025)
Peru has a high incidence and mortality rate of stomach and colorectal cancers. While chromoendoscopy (CE) with indigo carmine dye is the gold standard for gastrointestinal tumor early detection, its accessibility is limited in Peru due to cost and infrastructure restrictions. This study explores the potential of a natural alternative: anthocyanin dye extracted from purple corn (PC), a widely consumed and accessible food source in Peru. A PC decoction was prepared by boiling the PC and adjusting the pH to 8. A 38-year-old male patient underwent colonoscopy, finding a rectal polyp followed by CE with both IC and PC solution (PCS). The PCS effectively stained the colonic mucosa, allowing for visualization of the lesion. In this report, PCS is presented as a potential cost-effective and readily available natural contrast agent for CE, particularly relevant for low-resource environments in Peru. Further research and collaboration are needed to address standardization and staining duration for more reliable and accurate results.